Hanna's diary, 1938-1941 : Czechoslovakia to Canada - Spencer, Hanna (McGill-Queen's University Press, 2001)
"Hanna Fischl, a Czech of Jewish descent, was twenty-four when Hitler's shadow loomed over Europe in 1938. No longer able to associate openly with her lover, a Christian, she began writing a diary at his request to record her life during their time apart. Killed before the war ended, he never read the words she wrote. Hanna's Diary, 1938-1941 offers an intimate view of the events that engulfed Europe and the world, evoking the fear, desertion of friends, and sense of isolation that Hanna felt as Nazism spread."--Jacket.